Self-grown MnO2 nanosheets on carbon fiber paper as high-performance supercapacitors electrodes. (1st November 2016) - Dang, Wenhui; Dong, Chengjun; Zhang, Zhifang; Chen, Gang; Wang, Yude; Guan, Hongtao
Abstract: MnO2 was self-grown on carbon fiber paper (CFP) via a facile redox reaction, which is constructed by interconnected ultrathin nanosheets array. The CFP acts as both a supporting scaffold and a reducing agent for MnO2 growth. The obtained MnO2 /CFP composite was directly used as electrodes for supercapacitors, delivering a high specific capacitance of 713.7 F/g (0.5 A/g). Cyclic stability testing of the MnO2 /CFP electrode reveals 86.8% retention in specific capacitance after 1200 cycles at 5.0 A/g. The nanosheet morphology of the MnO2 on CFP brings about more efficient electroactive sites and facilitates the electrolyte penetration, allowing greater access for ions to active reaction sites. Hence, the attractive electrochemical performances exhibited by this MnO2 /CFP electrode endow them potentially promising candidates for supercapacitors.